Assistive technologies for managing language disorders in dementia - Klimova, Blanka; Maresova, Petra; Kuca, Kamil (Neuropsychiatric disease and treatment, 2016)
At present, the number of elderly people is rapidly increasing, which represents a significant threat in terms of their care when they fall ill. One of the most common aging diseases nowadays is dementia, whose symptoms sooner or later include loss of cognitive functioning. Cognitive disorders can vary from serious mental retardation to inability to recall things, to the loss or disorder of specific cognitive functions such as communication. These disorders not only affect the quality of people's own life but also impose a substantial burden on their families, particularly on their caregivers. Therefore, the aim of this article is to highlight the role of assistive technologies (ATs) for managing language impairments in dementia in order to improve patients' quality of life. In addition, ATs focused on training patients' memory are also mentioned, since they can help patients to maintain their language skills. Furthermore, these ATs can delay the need for institutional care, as well as significantly reduce costs on patient care. The importance of future research in the area of the development of ATs for managing the language impairments in dementia is also discussed. There is a general trend toward the personalization of patient needs and requirements in the area of ATs. For the purpose of this article, a method of literature review of available sources defining language disorders and providing characteristic features of language disorders in dementia is used. In addition, a method of comparison of different research studies exploring ATs focused on delaying language disorders in dementia in order to postpone patients' need for institutional care is also exploited.